2014
DOI: 10.1093/molbev/msu147
|View full text |Cite
|
Sign up to set email alerts
|

Paralogous Radiations of PIN Proteins with Multiple Origins of Noncanonical PIN Structure

Abstract: The plant hormone auxin is a conserved regulator of development which has been implicated in the generation of morphological novelty. PIN-FORMED1 (PIN) auxin efflux carriers are central to auxin function by regulating its distribution. PIN family members have divergent structures and cellular localizations, but the origin and evolutionary significance of this variation is unresolved. To characterize PIN family evolution, we have undertaken phylogenetic and structural analyses with a massive increase in taxon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
229
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(240 citation statements)
references
References 58 publications
11
229
0
Order By: Relevance
“…It must be noted that, until multiple additional genomes from charophyte and chlorophyte species have been sequenced, the presence of genes not detected in transcriptomes cannot be ruled out. However, when a similar dataset for liverworts and other bryophytes with an even lower coverage of the species space was used, all the symbiotic genes were recovered, in line with results obtained in the study of other processes (44)(45)(46) and lending support to our conclusions.…”
Section: Discussionsupporting
confidence: 89%
“…It must be noted that, until multiple additional genomes from charophyte and chlorophyte species have been sequenced, the presence of genes not detected in transcriptomes cannot be ruled out. However, when a similar dataset for liverworts and other bryophytes with an even lower coverage of the species space was used, all the symbiotic genes were recovered, in line with results obtained in the study of other processes (44)(45)(46) and lending support to our conclusions.…”
Section: Discussionsupporting
confidence: 89%
“…Also, if a canonical or long PIN protein was present in the last common ancestor of land plants [13], our data would suggest that PM-localized PIN proteins predate the origin of land plants.…”
Section: Resultsmentioning
confidence: 86%
“…Similar to that of the angiosperm Arabidopsis, the P. patens genome encodes two different types of PIN proteins, characterized by either a short or a long hydrophylic loop between the transmembrane regions ( Figure 1A), the latter designated as the canonical PIN protein [12,13]. We assessed the auxin transport capabilities of these different PIN proteins by several means.…”
Section: Resultsmentioning
confidence: 99%
“…This transport was later supported by the findings of Gaal et al (1982) and Maravolo (1976), who showed that 14 C-IAA is transported in an apical-basal and dorsal-ventral manner in the M. polymorpha thallus. Considering M. polymorpha has at least four PIN-FORMED (PIN) genes (Bennett et al, 2014a), these findings suggest PIN-mediated polar auxin transport is an important mechanism for gametophytic M. polymorpha development, as recently shown in the moss P. patens (Bennett et al, 2014b;Viaene et al, 2014). Our IAA measurements of different thallus tissues suggested IAA levels correlate well with pro YUC2:GUS expression but less well with pro TAA: GUS, as Mp-TAA is highly expressed only in the meristematic region and the base of gemma cups, with much weaker signal in the midrib and no signal in thallus margins.…”
Section: Meristematic Auxin Synthesis and Transport Regulates M Polymentioning
confidence: 99%